Macrophages expressing TREM-1 are involved in the progression of HPV16-related oropharyngeal squamous cell carcinoma. (1st January 2021) - Azzimonti, Barbara; Raimondo, Luca; Squarzanti, Diletta Francesca; Rosso, Tiziana; Zanetta, Paola; Aluffi Valletti, Paolo; Chiusa, Luigi; Masini, Laura; Pecorari, Giancarlo; Airoldi, Mario; Krengli, Marco; Giovarelli, Mirella; et al.
Abstract: Introduction: Many types of research have been performed to improve the diagnosis, therapy, and prognosis of oropharyngeal carcinomas (OP-SCCs). Since they arise in lymphoid-rich areas and intense lymphocytic infiltration has been related to a better prognosis, a TREM-1 putative function in tumour progression and survival has been hypothesized. Materials and methods: Twenty-seven human papillomavirus (HPV) 16 + OP-SCC specimens have been analyzed to relate TREM-1 expression with histiocytic and lymphocytic markers, HPV presence and patients' outcome. Results: No differences have been shown between intratumoral and stromal CD4 + cells, while intratumoral CD8 + lymphocytes are higher with respect to the tumour stroma ( p = .0005). CD68 + cells are more than CD35 + and TREM-1 + ; their presence is related to CD35 ± and TREM-1 ± histiocytes ( p = .005 and .026, respectively). Intratumoral CD4 + lymphocytes are higher in p16 + cases (11/27) than in p16 − ( p = .042); moreover, p16 positivity correlates to a better survival ( p = .034). CD4 +, CD8 + and CD35 + cells have no impact on survival, while CD68 expression heavily influences progression and bad outcome ( p = .037). TREM-1 positivity also leads to worst overall survival ( p = .001): peritumoral expression and death-cause relationship are always significant, particularly when the cause is OP-SCC ( p = .000). Conclusion: While p16 shows to better stratify HPV16 + patients' outcome, TREM-1 + macrophages suggest their key importance in HPV-related OP-SCCs progression. KEY MESSAGES: TREM-1 positivity correlates to the worst overall survival of HPV16-positive OPSCCs-affected patients. p16-positive HPV16 related OPSCCs patients have a better prognosis with respect to p16-negative ones.